2010
DOI: 10.1016/j.rmed.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Elevated 1, 25-dihydroxyvitamin D levels are associated with protracted treatment in sarcoidosis

Abstract: Summary Background Active vitamin D metabolite, 1, 25-dihydroxyvitamin D, has pleomorphic effects on both innate and acquired immunity. Sarcoid granuloma derived 1, 25-dihydroxyvitamin D leads to hypercalcemia, but the association of 1, 25-dihydroxyvitamin D with the clinical phenotype of the disease is currently unknown. Objective To determine the relationship between serum 1, 25-dihydroxyvitamin D levels and the degree of sarcoidosis disease chronicity. Design Serum 1, 25-dihydroxyvitamin D levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…This gene encodes a member of the cytochrome P450 superfamily. The enzyme activates vitamin D3, which has a well-established general immunoregulatory function [57,58] and also plays a role in lung immunity and in sarcoidosis [59,60]. Moreover, this gene has very recently been reported to be differentially expressed in sarcoidosis patients with a progressive-fibrotic, compared to a self-limiting, course of the disease [61].…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes a member of the cytochrome P450 superfamily. The enzyme activates vitamin D3, which has a well-established general immunoregulatory function [57,58] and also plays a role in lung immunity and in sarcoidosis [59,60]. Moreover, this gene has very recently been reported to be differentially expressed in sarcoidosis patients with a progressive-fibrotic, compared to a self-limiting, course of the disease [61].…”
Section: Discussionmentioning
confidence: 99%
“…44 A cross-sectional analysis of 100 patients with autoimmune disease showed that a similar dynamic seems to occur in autoimmune disease. 45 Confirmation of this observation has been demonstrated in Crohn's disease 46 and rheumatoid arthritis, 44 with Kavathia et al tying higher levels of 1,25-D to greater disease severity in sarcoidosis patients, 47 and Mawer et al finding that 1,25-D levels were particularly elevated in the synovial fluid surrounding the joints of subjects with rheumatoid arthritis. 48 We have previously predicted, based on molecular in silico emulation, that at higher concentrations, 1,25-D interferes with expression of several of the body's other key nuclear receptors, including the glucocorticoid receptor, the androgen receptor and the thyroid receptor.…”
Section: Communities Of Microbes Drive Autoimmune Diseasementioning
confidence: 73%
“…Предполагают, что 1,25(ОН) 2 D обладает иммунорегуляторными свой-ствами, подавляя, в частности, синтез IL-2 и γ-интерферона, участвующих в формировании сар-коидных гранулем и тем самым сдерживая некон-тролируемое гранулематозное воспаление [15]. Дру-гие авторы [16] считают, что внепочечная гиперпро-дукция 1,25(ОН) 2 D потенциируется цитокинами (в частности, γ-интерфероном) и повышенный уро-вень 1,25(ОН) 2 D отражает хроническое течение сар-коидоза. Описаны также случаи гиперкальциемии при саркоидозе на фоне нормального уровня 1,25(ОН) 2 D и повышенной концентрации PTHrP [3,10,17].…”
Section: Discussionunclassified